Efeitos biológicos in vitro de agentes físicos utilizados em fisioterapia - Meyer, Patrícia Froes (2008)
The uses of radiobiocomplexes labeled with technetium-99m contributed to health science advances. Stannous chloride (SnCl2) has been used as a reducing agent for the labeling process. Cytotoxic and genotoxic effect of the SnCl2 have been described in several studies and with this experimental models alterations in molecular and cellular level can be evaluated. In the last years the physicals therapists acquired new devices which emits electromagnetic radiation such us Extremely Low Frequency Pulsated Electromagnetic Fields (E.L.F. P.E.M.F.), radiofrequency, Intense Pulsed Light (I.P.L.) and others which emits sonic waves such us Biorresonance. Scientific evidence of the effects and dosage is important to protect public health and to reach exposition levels that result in significant biological effects. The aim of this project is to verify the effects of these physical agents in plasmid DNA and E. coli AB1157 cultures in presence or absence of SnCl2 and the effects in blood constituents labeled with technetium-99m. Wistar rats blood was exposed to the cited sources and the labelling of blood constituents with 99mTc was carried through. Cultures of E. coli AB1157 and plasmidial samples DNA had been also exposed the physical agents. The results suggest that these agents are capable of altering neither the survival of E. coli cells or plasmid DNA electrophoresis mobility. The multidiscipline character was clearly in this study due the interaction between Nuclear Medicine department of the UERJ and the Laboratory of Physical Agents of the Maimonides University in Argentina until the union between the teacher (biomedical and physiotherapist) and student (physiotherapist), besides collaborators of the area of Physics and Biology, promoting new ideas and perspectives and also adding the knowledge of different areas and origins